2010
DOI: 10.1523/jneurosci.3742-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortical Representation of Hand Translation and Rotation during Reaching

Abstract: Previous studies have shown that hand translation is well represented by neuronal activity in the proximal arm area of primary motor cortex (M1). However, little is known about cortical representation of hand rotation in M1. In this study, single-unit activity was recorded from monkeys while they performed a "center-out with rotation" task. When reaching for a target, subjects had to match four separate kinematic parameters: three-dimensional location and one-dimensional orientation of the target. Among the 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Multiplicative neuronal integration, known as gain fields, was first reported for neurons in posterior parietal cortex (LIP and 7a) (Andersen and Mountcastle, 1983;Andersen et al, 1985) and later found in many other areas in the brain, including subcortical structures (Lal and Friedlander, 1990;Van Opstal et al, 1995;Boussaoud et al, 1998;Wang et al, 2010). It has been theorized that such gain field encoding is beneficial for sensorimotor transformation from multiple neuronal inputs (Pouget and Sejnowski, 1997;Salinas and Sejnowski, 2001).…”
Section: Gain Field Encoding In the Primitivesmentioning
confidence: 99%
“…Multiplicative neuronal integration, known as gain fields, was first reported for neurons in posterior parietal cortex (LIP and 7a) (Andersen and Mountcastle, 1983;Andersen et al, 1985) and later found in many other areas in the brain, including subcortical structures (Lal and Friedlander, 1990;Van Opstal et al, 1995;Boussaoud et al, 1998;Wang et al, 2010). It has been theorized that such gain field encoding is beneficial for sensorimotor transformation from multiple neuronal inputs (Pouget and Sejnowski, 1997;Salinas and Sejnowski, 2001).…”
Section: Gain Field Encoding In the Primitivesmentioning
confidence: 99%
“…Grasp parameters, such as preshape, aperture, wrist orientation, grasp force and feedback control, should be involved in sensorimotor cortex to obtain a flexible grasp movement. Besides the grip type discussed in this paper, how grasp force [1,30], wrist orientation [17,33] and grasp aperture [12] are encoded in the brain were also studied before. However, a combination of these grasp factors was rarely mentioned, which are pivotal for dexterous control of prosthesis in BMI applications.…”
Section: Resultsmentioning
confidence: 99%
“…Using similar techniques and after being presented with a 3D brain control task (note: the subject had never seen a 3D center-out task prior to the closed-loop experiments), the subject gained very fast and accurate control in a manner of weeks. Finally, the subject was presented with a 4D task [83] where it had to control both the 3D translation and 1D rotation of a computer cursor. In a little over a month, the subject gained accurate control over a 4D cursor.…”
Section: Brain-computer Interfacesmentioning
confidence: 99%